Tensions between the Físico-Mor and the University of Coimbra: The Accreditation of Medical Practitioners in Ancien-Regime Portugal - Abreu, Laurinda (2018)
Institutional relations between the empirical and the academic medical worlds in early modern Portugal were strained over the accreditation of doctors and surgeons. The circumstances surrounding the development of the medical field are examined here from the accession of King Manuel I in 1495 until 1825, the year when the creation of the medical and surgical schools in Lisbon and Porto marked a new paradigm in the academic training of physicians and surgeons. The analysis draws on a relational database of more than 22,000 people who applied for a licence to practise their professions and/or were awarded public appointments (partidos). It focuses on the University of Coimbra and the chief physician (Físico-Mor)—two authorities created and controlled by the crown—and their conflict over the accreditation of medical practitioners during this period. The aim here is to broaden the study of the history of medicine in Portugal by pointing out the possible consequences of the attitudes held by the chief physician and the University of Coimbra. Throughout the period in question they both appeared to be motivated more by the desire to protect their own interests than by any scientific purpose.